A Comparative Study Between Public And Private Procurement System In Building Projects In Malaysia - Radzi, Nurhidayah Mohd (2012)
This thesis was undertaken to survey the perception and selection of client in Malaysia including the public and private sector on the types of procurement system „used‟ and „preferred‟, the problems arising based on the procurement „used‟ and also the satisfaction level between both sectors of client. The motivation to study the procurement systems in construction field are caused by the problems and many issues in the Malaysian construction industry recently. Since Malaysian construction industry is one of the components that give a massive impact on the national economy, procurement system are said to be correlate to this matter hence, needs to be revised. Personally Administered questionnaire survey were conducted over 4 months period in 2009 to get the population aim perception‟s on the procurement issues such procurement types „used‟ and „preferred‟, the problems of procurement types and the level of satisfaction between public and private sector clients. Interviews sessions were also conducted in order to strengthen the answers gathered in questionnaire survey session.